Blue Diversion: A New Approach To Sanitation In Informal Settlements - Larsen, Tove A.; Gebauer, Heiko; Gründl, Harald; Künzle, Rahel; Lüthi, Christoph; Messmer, Ulrike; Morgenroth, Eberhard; Niwagaba, Charles B.; Ranner, Bernhard (Journal of Water, sanitation and Hygiene for Development, 2015)
The sanitation concept ‘Blue Diversion’ (www.bluediversiontoilet.com) was developed as a possible answer to the sanitation crisis in urban slums. It is based on two main elements: (1) diversion of urine, feces, and water at the source as the basis for efficient resource recovery, and (2) linking different scales (family toilets and semi-centralized resource recovery). Our objective was to develop an attractive ‘grid-free’ (i.e. functioning without piped water, sewer, and electrical grid) dry urine-diverting toilet, which provides water (through recycling on-site) for flushing, personal hygiene (anal cleansing and menstrual hygiene), and hand washing. This service, including the entire sanitation value chain, should eventually be made available as a profitable business with total user fees of 5 ¢/p/d. The results presented in this paper are (1) a toilet design model, (2) the development of a new type of membrane bioreactor for treating flush and wash water, (3) main results of a geographic information system-based stochastic service model to link the family-scale toilet to a community-scale Resource Recovery Plant, and (4) a business model that yields maximum profit for the local community. We conclude that the approach is feasible, but challenging from a technical as well as an organizational point of view.
Keywords: innovation, resource recovery, source separation, toilet design, urban, wastewater treatment